2021
DOI: 10.1017/s135561772000140x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Concern after Acquired Brain Injury: The Role of Negative Emotion Recognition and Anger Misattribution

Abstract: Objective: Behavioral changes are common after acquired brain injury (ABI) and may be caused by social cognition impairments. We investigated whether impaired emotion recognition, specifically Negative Emotion Recognition (NER) and Anger Misattribution (AM), after ABI was related to behavioral problems, so-called Behaviors of Concern (BoC). Method: The study included 139 participants with ABI and 129 healthy controls. BoC was measured using four scales of the Brock Adaptive Functioning Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Therefore, following up on Jorna et al. (2021) who reported on impaired NER in ABI patients, we additionally performed the logistic regression analysis with only negative emotions (NER) as a predictor variable. However, NER did not significantly differentiate between diagnostic categories, whereas overall emotion recognition performance, pertaining to aggregated score on the whole range of emotional expressions, did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, following up on Jorna et al. (2021) who reported on impaired NER in ABI patients, we additionally performed the logistic regression analysis with only negative emotions (NER) as a predictor variable. However, NER did not significantly differentiate between diagnostic categories, whereas overall emotion recognition performance, pertaining to aggregated score on the whole range of emotional expressions, did.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study the recognition of disgust was impaired in AD patients, but preserved in MCI patients (Bediou et al., 2009). Specific impairments in NER were found to be associated with an increase in social behavioural problems in patients with acquired brain injury (ABI), as reported by informal caregivers (Jorna et al., 2021). Regarding MDD, in one meta‐analysis impaired recognition of the emotions anger, disgust, fear, happiness, and surprise was reported and no impairments in sadness (Dalili et al., 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, recipients (often unaware) search for indicators of honesty to separate reliable and unreliable sources. It expands the importance of behaviour assessment and non-verbal communication -even knowing that Albert Mehrabian overestimated the significance of facial channel in the overall impact of a message (Hegstrom, 1979;Mehrabian, Wiener, 1967;Mehrabian, Ferris, 1967), we agree that our cognition is oriented towards encoding facial expressions (Noah et al, 2020;Borod et al, 2002;Dailey et al, 2002;Jorna et al, 2021) and non-verbal messages mediate commitment towards communication (Asan et al, 2015).…”
Section: Introductionmentioning
confidence: 70%
“…1 In patient groups with acquired and traumatic brain injuries, inappropriate disinhibited social behavior and decreased social monitoring, as rated by close others, have indeed been found to be related to impaired emotion recognition. 10,17 Only a few studies investigated possible relations between specific "behaviors of concern" reported by proxies and impaired emotion recognition in AD dementia. 18 Poveda et al (2017) 19 found no associations among indices of apathy, agitation, irritability, and impaired emotion recognition.…”
mentioning
confidence: 99%
“…A more direct relation between increased aggressive and disinhibited behaviors, considered as problematic by close others, and impaired emotion recognition can be explained by patients not being able to perceive the emotional expressions of their close others, such as looking sad, frowning or being angry, which can be considered as stop signals for these behaviors 1 . In patient groups with acquired and traumatic brain injuries, inappropriate disinhibited social behavior and decreased social monitoring, as rated by close others, have indeed been found to be related to impaired emotion recognition 10,17 …”
mentioning
confidence: 99%